PENGEMBANGAN WAHANA WISATA JONGGOL DI DUSUN BALANGAN, WUKIRSARI, CANGKRINGAN - Putri Rachmawati; Linda Kusumastuti; Desi Susilawati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2019)
KKN-PPM is an empowerment program that will be implemented in Dukuh Balangan, Wukirsari Village, Cangkringan District, Sleman Regency, D.I. Yogyakarta aims to focus on the development and packaging of jonggol tourism vehicles in Balangan needs to be implemented to realize outbound education tours and camping ground. Which has selling power by highlighting the uniqueness, and the authenticity of nature around the Balangan hamlet? This service uses observation, interview, and education methods. In this educational method, the ESD method is used which provides counseling, socialization, training, and implementation. The result of dedication is the availability of outbound vehicles, garbage disposal, and places of worship/ so that tourist attractions can be better in tourism management, and a tool for sustainable tourism development.Keywords: KKN PPM, Observation, Interview, ESD (Education for Sustainable Development) method, Jonggol Tourism